Pengaruh Lingkungan Individu Mahasiswa dan Kinerja Bauran Pemasaran Perguruan Tinggi terhadap Proses Keputusan Mahasiswa dan Nilai Jasa Pendidikan Tinggi Komputer - Prabowo, Harjanto (Binus Business Review, 2011)
Colleges offering computer education are increasing, especially with the widespread use of information technology in all fields. This paper presents the results of research that aims to uncover the level of service marketing mix of performance conformity with the interests of education and expectations of students. Research conducted descriptive, while the research method used is the method of explanatory survey of 770 students and 54 leaders from computer private colleges in Jakarta. The results showed that the individuals environment is more influential on the decision process of selecting college students compared the performance of education services marketing mix. There is a gap between the performance of the marketing mix of educational services with the level of expectation and perceived level of student interest. Therefore, leaders of computer private colleges in Jakarta should pay attention to changes in consumer behavior to marketing mix program of education services can further enhance the value of education services.